Barriers to Hospital Pharmacy Information System – An emerging concern - Jacson, Janice; Sebastian, Stephy (Indian Journal of Pharmacy & Drug Studies, 2023)
Pharmacy plays an important role in keeping up with the clinical care of patients. In a hospital setting the pharmacies revolve around medication demands and catering to their ever-increasing prices. Such factors cause inefficiencies in the availability of information systems. PubMed and Google scholar databases were studied and extracted for getting information on the technology used in pharmacies. Ongoing vendor involvement, acknowledgement of technology limitations, and attempts to address them were crucial in overcoming technology barriers. This review aims to provide the importance of information systems and implement them across various hospitals.